Releasing number of Telenomus remus (Nixon) (Hymenoptera: Platygastridae) against Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) in corn, cotton and soybean - Pomari, Aline Farhat; Bueno, Adeney De Freitas; Bueno, Regiane Cristina Oliveira De Freitas [UNESP]; Menezes Junior, Ayres De Oliveiras; Fonseca, Augusto Cesar Prado Fernandes (Universidade Federal de Santa Maria, 2013)
Telenomus remus releasing numbers may vary depending on the crop, plant architecture and/or the plant phenological stage. Thus, we examined the number of parasitoids needed for effective pest control of Spodoptera frugiperda on corn, cotton and soybean. In all crops, the parasitism response in relation to increasing numbers of the parasitoids had a quadratic effect. In corn, the maximum parasitism observed was 99.8% and 96.8% at a parasitoid releasing number of 0.231 and 0.264 T. remus females per S. frugiperda egg at phenological stages V4 and V10, respectively. Differently, in cotton and soybean, the highest parasitim were recorded using the highest tested T. remus releasing numbers (0.297 parasitoid per S. frugiperda egg). In cotton, it was 77.8% and 73.1% at the vegetative and reproductive stages, respectively and in soybean, it was 77.3% and 54.4% also at the vegetative and reproductive stages. Thus, the appropriated T. remus releasing number might vary accordingly to the crop and plant phenological stage, being higher for soybean and cotton and lower for corn.

O número de Telenomus remus a ser liberado pode ser variável, dependendo de cada cultura, da arquitetura da planta e/ou do seu estágio fenológico. Assim, foi examinado o número de parasitoides necessários para obter o controle efetivo de Spodoptera frugiperda em milho, algodão e soja. Em todas as culturas, a resposta do parasitismo em relação ao número crescente de parasitoides teve um efeito quadrático. Em milho, o parasitismo máximo observado foi de 99,8% e 96,8% em um número de parasitoides liberados de 0,231 e 0,264 fêmeas de T. remus por ovo de S. frugiperda nos estádios fenológicos V4 e V10, respectivamente. Diferentemente, em algodão e soja, os maiores parasitismos foram verificados liberando o maior número de fêmeas de T. remus testados (0,297 fêmeas por ovos de S. frugiperda). Em algodão, foi 77,8% e 73,1% nos estágios vegetativo e reprodutivo, respectivamente e, em soja, foi 77,3% e 54,4% também nos estágios vegetativo e reprodutivo. Assim, o número apropriado de T. remus a ser liberado pode variar de acordo com a cultura e com o estágio fenológico da planta, sendo mais elevado para soja e algodão e mais baixo para milho.
Número de Telenomus remus Nixon (Hymenoptera: Platygastridae) a ser liberado para controle de Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) em milho, algodão e soja
Keywords: biological control; parasitoid density; parasitism; controle biológico; densidade de parasitoides; parasitismo